Identifikasi Pola Bilangan Pada Kain Tenun Amfoang Utara (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
Identification of number patterns on North Amfoang woven fabric This research is a qualitative research that aims to identify the pattern of numbers on the woven fabric of North Amfoang, Kupang Regency when viewed from what number patterns exist in the woven fabric of the North Amfoang Community, Kupang Regency. The research was conducted in Kolabe Village, North Amfoang sub-district, Kupang district, with the object of research being the woven fabric of the North Amfoang community and the subject of the research were weavers. The instrument in this study used interview guidelines and documentation guidelines, The results of this study indicate that there is a mathematical value in woven fabrics when viewed from the aspect of number patterns on woven fabrics. The number patterns found in woven fabrics are odd number patterns and even number patterns
Keywords: Budaya lokal, kain tenun, pola bilangan